25-Hydroxyvitamin D Deficiency Is Associated With Inflammation-Linked Vascular Endothelial Dysfunction in Middle-Aged and Older Adults - Jablonski, Kristen L.; Chonchol, Michel; Pierce, Gary L.; Walker, Ashley E.; Seals, Douglas R. (Hypertension (Dallas, Tex. 1979), 2011)
We tested the hypothesis that vascular endothelial function, assessed by endothelium-dependent dilation, is related to serum vitamin D status among middle-aged and older adults without clinical disease, and that this is linked to inflammation. Brachial artery flow-mediated dilation, a measure of endothelium-dependent dilation, was lower (P<0.01) in vitamin D–insufficient (3.7±0.2%; serum 25-hydroxyvitamin D [25(OH)D]20 to 29 ng/mL; 62±1 years of age; n=31; mean± SE) and vitamin D–deficient (3.2±0.3%; 25(OH)D<20 ng/mL; 63±2 years of age; n=22) versus vitamin D–sufficient (4.6±0.4%; 25(OH)D>29 ng/mL; 61±1 years of age; n=22) subjects, whereas endothelium-independent dilation (brachial dilation to sublingual nitroglycerine) did not differ (P=0.45). Among all subjects, brachial flow-mediated dilation was positively related to serum 25(OH)D (%Δr=0.35; P<0.01) but not 1,25-dihydroxyvitamin D (r=−0.06; P=0.61), the active form of vitamin D. Vascular endothelial cell expression of the proinflammatory transcription factor nuclear factor κB was greater in deficient versus sufficient subjects (0.59±0.07 versus 0.44±0.05; P<0.05), and inhibition of nuclear factor κB (4 days oral salsalate) improved flow-mediated dilation to a greater extent in subjects with lower versus higher 25(OH)D (+3.7±0.6 versus +2.0±0.2%; P<0.05). Endothelial cell expression of the downstream proinflammatory cytokine interleukin-6 also was higher in deficient versus sufficient subjects (0.67±0.08 versus 0.47±0.05; P<0.01) and inversely related to serum 25(OH)D level (r=−0.62; P<0.01), whereas vitamin D receptor and 1-α hydroxylase, the 25(OH)D to 1,25-dihydroxyvitamin D converting enzyme, were lower (P<0.05). Inadequate serum 25(OH)D is associated with vascular endothelial dysfunction among healthy middle-aged/older adults, and this is mediated in part by nuclear factor κB–related inflammation. Reduced vitamin D receptor and 1-α hydroxylase may be molecular mechanisms linking vitamin D insufficiency to endothelial dysfunction.